Impact of karyotype organization on interlocus recombination between T cell receptor genes in Equidae - Drbalova, Jitka; Musilova, Petra; Kubickova, Svatava; Sebestova, Hana; Vahala, Jiri; Rubes, Jiri (Cytogenetic and genome research, 2014)
The T cell receptor (TCR) genes (TRA, TRB, TRD and TRG) reside in 3 different chromosomal regions. During the maturation of T lymphocytes, the TCR genes are rearranged by site-specific recombination, a process that also predisposes T cells to aberrant rearrangements. Illegitimate recombination between the TCR genes occurs at a low level in healthy individuals, but this frequency may correlate with the risk of lymphoma. The aim of this work was to investigate interlocus recombination in equids. Illegitimate rearrangements were studied in peripheral blood lymphocytes by FISH with painting and BAC probes and by sequencing of PCR products, and the frequencies of recombination were assessed in horses and 4 other equids. The presence of several trans-rearrangement products between the TRA and TRG genes was verified by PCR in all investigated equids. Frequencies of trans-rearrangements in horses are higher than in humans, and colocalization of the TCR genes on the same chromosome increases the incidence of trans-rearrangements between them. The orientation of the TCR genes does not impact interlocus recombination itself but does affect the viability of cells carrying its products and consequently the number of trans-rearrangements observed in lymphocytes.
Keywords: Cell Survival; karyotyp; homologní rekombinace; Humans; geny TcR; Lymphocytes; lymfocyty; Genes, T-Cell Receptor; Female; viabilita buněk; genová přestavba T-lymfocytů; body zlomu chromozomu; Homologous Recombination; lidé; zvířata; Cells, Cultured; Swine; malování chromozomů; Chromosome Painting; Chromosome Breakpoints; ženské pohlaví; Karyotype; Male; kultivované buňky; Equidae; Gene Rearrangement, T-Lymphocyte; Animals; mužské pohlaví; prasata